2011
DOI: 10.1515/ijamh.2011.047
|View full text |Cite
|
Sign up to set email alerts
|

Asthma and quality of life in adolescents in Manisa, Turkey

Abstract: Background:The aim of this study was to determine the prevalence of asthma and the association between asthma and quality of life in sixth, seventh, and eighth graders in the city of Manisa. Method: The population of this cross-sectional study includes the sixth, seventh, and eighth grades of primary schools located in the city of Manisa (n = 59, 135). The study sample included 763 students from nine schools with different socioeconomic features selected by the Directorate of National Education. Data were coll… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 18 publications
(17 reference statements)
0
6
0
2
Order By: Relevance
“…After controlling for gender, age, negative affect, and number of co-morbid medical problems in adults, the physical concerns factor of anxiety sensitivity (AS-Physical Concerns) significantly predicted asthma control and influenced all domains of asthma-related QOL (symptoms, activity limitations, emotional functioning, and environmental stimuli) [ 14 ]. Asthma severity also affects QOL in adolescents, as has been reported in several studies from different countries [ 15 18 ]. Personality traits were significantly related to QOL of adolescents with asthma.…”
Section: The Effects Of Severe Asthma On Qol In Relation To Differentmentioning
confidence: 76%
“…After controlling for gender, age, negative affect, and number of co-morbid medical problems in adults, the physical concerns factor of anxiety sensitivity (AS-Physical Concerns) significantly predicted asthma control and influenced all domains of asthma-related QOL (symptoms, activity limitations, emotional functioning, and environmental stimuli) [ 14 ]. Asthma severity also affects QOL in adolescents, as has been reported in several studies from different countries [ 15 18 ]. Personality traits were significantly related to QOL of adolescents with asthma.…”
Section: The Effects Of Severe Asthma On Qol In Relation To Differentmentioning
confidence: 76%
“…This meta-analysis included 4 studies from Turkey, Sri Lanka, Finland and Germany, and all studies had a cross-sectional study design. (17,(34)(35)(36) The latter study used a QoL-instrument that measured mental wellbeing (in the meta-analysis interpreted as psychological functioning)…”
Section: Discussionmentioning
confidence: 99%
“…Overall, 15 studies (78.9%) were assessed as average quality (Altiparmak et al, 2011;Covaciu et al, 2013;Danansuriya & Rajapaksa, 2012;French et al, 1994;French, et al, 1998;Gau et al, 2010;Grootenhuis et al, 2007;Hallstrand et al, 2003;Hatzmann et al, 2008;Hutchings et al, 2007Hutchings et al, , 2008Kojima et al, 2009;Montalto et al, 2004;Sawyer et al, 2001;Van Gent et al, 2007;Wang et al, 2012) and four studies (21.1%) as high quality (Matterne et al, 2011;Merikallio et al, 2005;Moreira et al, 2013;Upton et al, 2005). The main reasons for low quality scores were the use of nonrepresentative samples (e.g., convenience sampling methods, 57.9%), no description of controls' health status (57.9%), response rates lower than 80% or not reported (84.2%), and the use of different procedures/settings in the completion of QoL questionnaires (52.6%).…”
Section: Methodological Qualitymentioning
confidence: 99%
“…Of the 19 included studies, 17 (reported in 18 articles; Altiparmak, Altiparmak, & Sari, 2011;Covaciu, Bergström, Lind, Svartengren, & Kull, 2013;Danansuriya & Rajapaksa, 2012;French, Christie, & Sowden, 1994;French, Carroll, Christie, 1998;Grootenhuis, Koopman, Verrips, Vogels, & Last, 2007;Hallstrand, Curtis, Aitken, & Sullivan, 2003;Hutchings et al, 2007Hutchings et al, , 2008Kojima et al, 2009;Matterne, Schmitt, Diepgen, & Apfelbacher, 2011;Merikallio, Mustalahti, Remes, Valovirta, & Kaila, 2005;Montalto, Bruzzese, Moskaleva, Higgins-D'Alessandro, & Webber, 2004;Moreira et al, 2013;Sawyer et al, 2001;Upton et al, 2005;Van Gent et al, 2007;Wang, Wang, Wang, Xu, & Zhang, 2012) examined the QoL of 32,874 children and adolescents and four studies (Gau et al, 2010;Hatzmann, Heymans, Ferrer-i-Carbonell, Van Praag, & Grootenhuis, 2008;Moreira et al, 2013;Van Gent et al, 2007) examined the QoL of 8,062 parents, from 13 different countries. The study design and sample characteristics are detailed in Table 2.…”
Section: Study Characteristicsmentioning
confidence: 99%